Regional fragility in the context of sustainable development: factors, methods, and the case of Ukraine (Economics and region, 2025)
This article explores the concept of regional fragility and the methods used to assess it. It identifies key factors contributing to regional fragility, including political instability, economic vulnerability, and security risks. Special attention is given to the Fragile States Index (FSI), which is calculated based on four core dimensions: cohesion, economic performance, political stability, and social well-being. The study emphasizes the potential for adapting individual components of the FSI to the regional level of analysis and presents an assessment of regional fragility across Ukraine. The research includes a visualization of the ranking results for the ten most vulnerable regions and provides a rationale for selecting these specific oblasts for in-depth analysis. Furthermore, the article outlines the indicators used to calculate an integrated fragility index tailored for regional evaluation within the framework of sustainable development. The article provides a detailed overview of the conceptual framework for understanding regional fragility in the context of sustainable development. It introduces a methodological approach for quantifying fragility using adapted indicators from the Fragile States Index. The methodology includes both quantitative and qualitative approaches, combining statistical analysis with structured indicator-based evaluation. Particular emphasis is placed on the use of composite indices and multi-criteria decision-making methods to ensure a comprehensive assessment of regional fragility. The article also reviews the role of international organizations such as the Fund for Peace, the OECD, and the World Bank in developing and applying fragility assessment frameworks. These global practices serve as a foundation for adapting tools to the Ukrainian context and enhancing the relevance of regional policy responses. The study also highlights the spatial disparities in regional vulnerability across Ukraine. By integrating global practices with localized data, the research offers a practical tool for policymakers and regional planners. A separate section is devoted to analyzing international practices in assessing regional fragility. The value of this study lies in its methodological contribution—adapting national-level fragility assessment tools to the regional context, thereby enhancing the analytical capacity for sustainable regional development planning.
Keywords: fragility index; sustainable development; region; ranking; regional fragility; risk